Development and Psychometric Properties of the Test of Passive Aggression - Schanz, Christian G.; Equit, Monika; Schäfer, Sarah K.; Käfer, Michael; Mattheus, Hannah K.; Michael, Tanja (Frontiers in Psychology, 2021)
Background: To date, most research on aggression in mental disorders focused on active-aggressive behaviour and found self-directed and other-directed active aggression to be a symptom and risk-factor of psychopathology. On the other hand, passive-aggressive behaviour has been investigated less frequently and only in research on psychodynamic defence mechanisms, personality disorders, and dysfunctional self-control processes. This small number of studies primarily reflects a lack of a reliable and valid clinical assessment of passive-aggressive behaviour. To address this gap, we developed the Test of Passive Aggression (TPA), a 24-item self-rating scale for the assessment of self-directed and other-directed passive-aggressive behaviour. Method: Study 1 examined the internal consistency and factorial validity of the TPA in an inpatient sample (N = 307). Study 2 investigated the retest-reliability, internal consistency, and construct validity (active aggression, personality traits, impulsivity) of the TPA in a student sample (N = 180). Results: In line with our hypothesis, Exploratory Structural Equation Modelling revealed an acceptable to good fit of a bi-factorial structure of the TPA (Chi-square-df-ratio = 1.98; RMSR = .05). Both TPA scales showed good to excellent internal consistency (α = .83– .90) and four-week retest-reliability (rtt = .86). Correlations with well-established aggression scales, measures of personality, and impulsivity support discriminant and convergent validity of the TPA. Conclusions: The TPA is a reliable and valid instrument for the assessment of self-directed and other-directed passive-aggressive behaviour.